2019
DOI: 10.1029/2019jc015040
|View full text |Cite
|
Sign up to set email alerts
|

ISOW Spreading and Mixing as Revealed by Deep‐Argo Floats Launched in the Charlie‐Gibbs Fracture Zone

Abstract: To improve our understanding of deep circulation, we deployed five Deep‐Argo floats (0–4,000 m) in the Charlie‐Gibbs Fracture Zone (CGFZ), which channels the flow of Iceland‐Scotland Overflow Water (ISOW), a dense water mass of the North Atlantic Ocean. The floats were programed to drift at 2,750 dbar in the ISOW layer. The floats mainly moved westward in the CGFZ, although some of them followed different routes for few cycles depending on northward intrusions of the North Atlantic Current over the CGFZ. One f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 62 publications
3
30
0
Order By: Relevance
“…The floats drifted in the core of ISOW at 2750 m. Based on the mean circulation scheme of Daniault et al (2016), we expected that all the floats would veer northward downstream of the CGFZ and flow cyclonically in the Irminger Sea. However, Racapé et al (2019) showed that none of the floats reached the Irminger Sea and one float even revealed a new direct route from ISOW toward the subtropical gyre without looping in the Irminger Sea. Oxygen data acquired by the floats showed that the ISOW layer was mainly composed of highly oxygenated ISOW and less oxygenated North East Atlantic Deep Water (NEADW), a complex water mass from the East Atlantic.…”
Section: Scientific Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The floats drifted in the core of ISOW at 2750 m. Based on the mean circulation scheme of Daniault et al (2016), we expected that all the floats would veer northward downstream of the CGFZ and flow cyclonically in the Irminger Sea. However, Racapé et al (2019) showed that none of the floats reached the Irminger Sea and one float even revealed a new direct route from ISOW toward the subtropical gyre without looping in the Irminger Sea. Oxygen data acquired by the floats showed that the ISOW layer was mainly composed of highly oxygenated ISOW and less oxygenated North East Atlantic Deep Water (NEADW), a complex water mass from the East Atlantic.…”
Section: Scientific Resultsmentioning
confidence: 93%
“…The deoxygenation of the ocean is a major concern in the context of climate change (Keeling et al, 2010), and the Deep-Arvor float is therefore equipped with an oxygen sensor to monitor oceanic oxygen content. In addition, dissolved oxygen concentration (referred to as O 2 in the following) is a classic parameter in oceanography, useful for gaining insight into biogeochemical (e.g., Riser and Johnson, 2008) and physical oceanic processes (Piron et al, 2016;Racapé et al, 2019). O 2 data are also important for operational oceanography that aims at monitoring and predicting the biogeochemical state of the ocean and marine ecosystems (Brasseur et al, 2009;Biogeochemical-Argo Planning Group, 2016;Le Traon et al, 2019).…”
Section: Deep Floats With Oxygen Sensors In the North Atlantic Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…The study further shows that in the model, most of the ISOW passing through the CGFZ follows this path, with a much lower fraction turning northward into the Irminger Sea. More recently, Racapé et al 19 reported that one of the five Deep-Argo floats initialized in the CGFZ followed a direct westward route from the CGFZ to the Flemish Cap, where it was able to join the Deep Western Boundary Current.…”
mentioning
confidence: 99%